Early childhood literacy skills: Implementation of the local genius-based steam learning model - Suryaningsih, Ni Made Ayu; Poerwati, Christiani Endah; Lestari, Putu Indah; Parwata, Made Yoga (Indonesian Journal of Educational Development (IJED), 2025)
Literacy skills are a key focus in the Merdeka Curriculum, with the development of children's literacy being fostered through engaging activities. Innovative learning models that allow children to explore their potential freely play a crucial role in this process. One such model is the Science, Technology, Engineering, Art, and Mathematics (STEAM) Learning Model, which can serve as both an approach and the core of early childhood education. Research on this topic is increasingly diverse and complementary. This study focuses on the implementation of the STEAM learning model, using Local Genius as the learning theme. The aim of this research was to evaluate the effect of the STEAM model based on Local Genius on early childhood literacy skills. Using a post-test only control group design with a quasi-experimental approach, data were collected through observation and analyzed using one-way analysis of variance (ANOVA). The results revealed an F value of 5.612 with a significance of 0.025 (sig < 0.05), indicating that the STEAM Learning Model based on Local Genius significantly influences early childhood literacy skills. Based on these findings, it is recommended that educators implement the STEAM Learning Model, incorporating local cultural elements, to enhance literacy skills in early childhood education.